The effect of blood ketone concentration and exercise intensity on exogenous ketone oxidation rates in athletes - Dearlove, DJ; Harrison, OK; Hodson, L; Jefferson, A; Clarke, K; Cox, PJ (Lippincott, Williams & Wilkins, 2020)
INTRODUCTION:Exogenous ketones potentially provide an alternative, energetically advantageous fuel to power exercising skeletal muscle. However, there is limited evidence regarding their relative contribution to energy expenditure during exercise. Furthermore, the effect of blood ketone concentration and exercise intensity on exogenous ketone oxidation rates is unknown. METHODS:Six athletes completed cycling ergometer exercise on three occasions within a single-blind, random order controlled, crossover design study. Exercise duration was 60 min, consisting of 20 min intervals at 25%, 50% and 75% maximal power output (WMax). Participants consumed either: i) bitter flavoured water (control); ii) a low dose β-hydroxybutyrate (βHB) ketone monoester ((KME); 252 mgkg BW, 'low ketosis'); or iii) a high dose βHB KME (752 mgkg BW, 'high ketosis'). The KME contained a C isotope label, allowing the determination of whole-body exogenous βHB oxidation rates through sampled respiratory gases. RESULTS:Despite an approximate doubling of blood βHB concentrations between low and high ketosis conditions (~2 mM versus ~4.4 mM), exogenous βHB oxidation rates were similar at rest and throughout exercise. The contribution of exogenous βHB oxidation to energy expenditure peaked during the 25% WMax exercise intensity but was relatively low (4.46 ± 2.71%). Delta efficiency during cycling exercise was significantly greater in the low ketosis (25.9 ± 2.1%) versus control condition (24.1 ± 1.9%; p=0.027). CONCLUSION:Regardless of exercise intensity, exogenous βHB oxidation contributes minimally to energy expenditure and is not increased by elevating circulating concentrations above ~2 mM. Despite low exogenous βHB oxidation rates, exercise efficiency was significantly improved when blood βHB concentration was raised to ~2 mM.